If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 2sin(5x + -3) Multiply f * x fx = 2sin(5x + -3) Reorder the terms: fx = 2ins(-3 + 5x) fx = (-3 * 2ins + 5x * 2ins) fx = (-6ins + 10insx) Solving fx = -6ins + 10insx Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -6insx-1 + 10ins Simplifying f = -6insx-1 + 10ins Reorder the terms: f = 10ins + -6insx-1
| 24=5(2x+5) | | 3h+2h-3=91.50 | | 6x-7=3x-5 | | 5x-xy=9y^2 | | 4x-3=x+54 | | t^3-t^2+t-4=0 | | 5x^2-10x+8=0 | | 4t^3-39t^2+36t+4=0 | | 36x-18-90x+60=-6 | | z*7-5=5 | | 4y-16=1 | | 9p-22.5= | | 25=10x-75 | | t*4-6=12 | | t*4=6-12 | | 5+4+0=544 | | a*3+2=14 | | 0.01*(y+12)-0.12=0.01*(5y+12) | | 24x-24-6=18x+18 | | 9m-29=34 | | y=2ax-3bx | | x^3-6x^2+3x+9=0 | | -4y-9=-1 | | 3x+8=69-3x | | 3x-4=5x+12x | | U^3+6u+1=3 | | (-3y-3)*(-8)= | | 5ln(x+4)= | | 7+78x=39x+10 | | -2x+4=-8+25x | | 12x-5-3x+5= | | 5x+29=2x+119 |